PENGARUH STUDI LANJUT DAN KEPUASAN KERJA TERHADAP KINERJA MELALUI MOTIVASI KERJA PEGAWAI PADA PT. BANK PEMBANGUNAN DAERAH JAWA TIMUR Tbk. CABANG MALANG - Fhirlie; Rosid; Mulyono, Sugeng; Hariono, Jefri (JUMBA (Jurnal Manajemen, Bisnis, dan Akuntansi), 2023)
The objectives of this study are: i) to prove and analyse the effect of further study on employee work motivation at PT. Bank Jatim Malang Branch, ii) to prove and analyse the effect of satisfaction on employee work motivation at PT. Bank Jatim Malang Branch, iii) to determine the effect of work motivation on performance at PT. Bank Jatim Malang Branch, iv) to determine the effect of further study on employee performance at PT. Bank Jatim Malang Branch. Bank Jatim Branch Malang, v) to determine the effect of job satisfaction on the performance of PT. Bank Jatim Branch Malang, vi) to determine the effect of further studies on performance through employee work motivation at PT. Bank Jatim Branch Malang, vii) to determine the effect of further studies on performance through employee work motivation at PT. Bank Jatim Branch MalangThis research is a type of quantitative research, which is a process of finding knowledge that uses data in the form of numbers as a means of finding information about what you want to know.The results showed that: Effect of further study (X1) on work motivation (Z), Effect of job satisfaction (X2) on work motivation (Z), Effect of work motivation (Z) on performance (Y), Effect of further study (X1) on performance (Y), Effect of commitment (X2) on performance (Y), Effect of further study (X1) through work motivation (Z) on performance (Y), Effect of job satisfaction (X2) through work motivation (Z) on performance (Y).